KERAGAMAN GENETIKA RAMIN [GONYSTYLUS BANCANUS (MIQ.) KURZ] DARI PROVINSI RIAU BERDASARKAN PROFIL RANDOM AMPLIFIED POLYMORPHIC DNA - Kusumadewi, Yulita; Poerba, Yuyu S.; Partomiharjo, Tukirin (Perhimpunan Biologi Indonesia, 2010)
ABSTRACTGenetic Diversity of Ramin [Gonystylus bancanus (Miq.) Kurz] from Riau Province Based onRandom Amplified Polymorphic DNA Fingerprint. Gonystylus bancanus is a commercialtimber found only on peat swamp forests, scatteredly distributed in Sumatra and Kalimantan.Their existence is now under severe threat due to habitat conversion. One of the remainingnatural populations of ramin was in Riau Province, Sumatra. This study aimed to assessgenetic diversity of this species within their natural populations in Riau Province using RandomAmplified Polymorphic DNA (RAPD). RAPD profiles were obtained by performing PCRamplification using five arbitrary primers. One hundred and eleven putative loci of RAPD werescored and analysed using Popgene and NTSYS software. Eleven of RAPD bands werecommonly found in all populations and 16 bands were distinctively found in certain populations.These unique bands may serve as population diagnostic marker for such populations. Theaverage genetic diversity within population (0.1606) was lower than that of among populations(0.1894). Genetic differentiation (Gst) indicated that 95.56% of total genetic diversity in raminwas attributed to the differences among populations. The highest genetic diversity was foundin population 3 (He:0.1858) and 3 (I:0.2864), while the lowest genetic variation was observed inpopulation 1 (He: 0.1438) and 2 (I: 0.2201). Total genetic diversity for all population (Ht) was0.1982 with an average value of genetic diversity within populations (Hs) was 0.1606. The lowlevel of genetic diversity found in ramin with high population differentiation may suggest thatthese remaining populations was undergoing genetic bottleneck resulted from severe habitatfragmentation.Keywords: genetic diversity, populations, ramin, Gonystylus bancanus, RAPD.